A method for the characterization of the reflectance of anisotropic functional surfaces. (25th May 2018) - Regi, F; Nielsen, J B; Li, D; Zhang, Y; Frisvad, J R; Aanæs, H; Tosello, G
Abstract: The functional properties of micro-structured surfaces have gained increasing interest thanks to many applications such as wetting, adhesion, thermal and/or electrical conductivity. In this study, directional optical properties, i.e. contrast between two regions of a surface, were achieved with an anisotropic microstructure composed of a close array of ridges. The anisotropic surface, designed as a combination of ridges, has been milled on a steel bar and replicated through hot embossing of Acrylonitrile butadiene styrene (ABS) and through replica technology using silicone rubber. The directional reflectance of the surface for a range of design-specific view-illumination configurations was determined using a method that involves a Hirox RH-2000 digital microscope, used as a gonioreflectometer. This method allows the empirical determination of the optimum surface microstructure for maximizing contrast between two horizontally orthogonal views. The results show that even if the uncertainty related to the instrumentation is up to 20% in some cases, this procedure is suitable for the characterization of the surface of both metal and plastic counterpart.